Management of BPH Using Cultural Techniques Experienced from Bangladesh (South Asian Journal of Agriculture, 2025)
A series of experiments was conducted in three Agro-Ecological Zones, namely AEZ 11, AEZ 12, and AEZ 13, at Khulna Metropolitan Thana, Dumuria, and Batiaghata Upazila under Khulna District of Bangladesh, to comprehend the incidence pattern of Brown Plant Hopper (BPH) in relation to cultural factors during the wet season rice (T. Aman) and dry season rice (Boro). The incidence of BPH at different growth stages of the rice crop and the number of affected/non-affected hills, together with rice yields, were evaluated. Two peaks of BPH were reported during the year, the first one during March-April and the other during September-October. Older rice plants received a higher number of BPH than young rice plants. Among the five arrangements of missing hills, 7 lines + missing line offered the best performance. In the case of five spacing arrangements, 20 cm × 30 cm spacing was the most suitable against BPH. The increase in the dose of urea fertilizer from recommended doses could cause higher BPH infestation. Among the five wet rice varieties, BRRI dhan49, BRRI dhan62, and BRRI dhan72 performed better, while among the five varieties in Boro, BRRI dhan58 performed the best, followed by BRRI dhan28, BRRI dhan47, BRRI dhan50, and BINA dhan8 against BPH. Among the five manipulation tactics against BPH, recommended dose of chemical fertilizer, spacing, chemical control, bili, and draining out water from the rice field treatment showed the lowest number of affected hills at all phases of rice with maximum yield compared to other treatments. In conclusion, this study offers a comprehensive incidence pattern of BPH in the rice grown areas that might help to manage in a comprehensive manner without affecting the environment.South Asian J. Agric., Vol. 10, No.1-2, 2024: 72-81